ANTI-HEMOLYTIC PROPERTY OF LOCAL MEDICINAL PLANT(S) UPON PAKISTANI COBRA VENOMINDUCED HEMOLYSIS - M. H. H. B. Asad; D. E. Sabih; B. A. Chaudhory; I. Ahmad; M. S. Hussain; N. Izhar; N. Akmal; A. H. Shahzad; I. Hussain (Journal of Animal and Plant Sciences, 2014)
Present study was carried out to assess scientifically anti-hemolytic properties of medicinal plants against Pakistani cobra induced hemolysis. Venom from Naja naja and Naja naja karachiensis were found to destabilize human red blood corpuscles membrane (HRBC) however, the effect of later was  found somewhat severe. Against Naja naja karachiensis venom twenty six medicinal plants of Pakistan were evaluated but only Cedrus deodara G. Don (P˃0.5) was proved the most effective (72%) in stabilizing HRBC membranes. Althaea officinalis Linn, Calotropis procera (Wild.) R.Br, Citrus limon (L). Burm. f, Enicostemma hyssopifolium (Willd.) Verdoorn, Leucas capitata Desf and Stenolobium stans (L) D. Don were found anti-hemolytic (0.5˃P˃0.1) at various concentration range (20 to 320 µg/mL) in comparison with standard anti-sera (56%). Flowers extract of Calotropis procera (Wild.) R.Br and bulbs of Allium cepa L were found helpful to neutralize snake venom hemolysis at P˂0.1. However, remaining plants extract (p˂0.05) were found to be hemolytic and potentiated the effect of venom instead of having anti-hemolytic potentials. On scientific basis this study emphasizes to rationalize, the use of listed medicinal plants in traditional system of medicine as an anti-hemolytic. Nevertheless, further study is inevitable to identify and isolate bio-active compound(s) from above cited potential medicinal plant(s) extract.
Keywords: Pakistani plants; Anti-hemolytic; Antidote; venom; Naja naja karachiensis; Naja naja